2014
DOI: 10.1016/j.bmcl.2014.04.087
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and SAR of a novel series of metabotropic glutamate receptor 5 positive allosteric modulators with high ligand efficiency

Abstract: We report the optimization of a series of novel metabotropic glutamate receptor 5 (mGlu5) positive allosteric modulators (PAMs) from a 5,6-bicyclic class of dihydropyrazolo[1,5-a]pyridin-4(5H)-ones containing a phenoxymethyl linker. Studies focused on a survey of nonamide containing hydrogen bond accepting (HBA) pharmacophore replacements. A highly potent and selective PAM, 2-(phenoxymethyl)-6,7-dihydropyrazolo[1,5-a]pyridin-4(5H)-one 11, VU0462054), bearing a simple ketone moiety, was identified (LE = 0.52, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These mutagenesis studies pointed to a common location for allosteric binding pockets for group I mGlu receptors. Additional studies have shown that residues at positions 3.40 and 7.38 are important for allosteric modulation of both mGlu 1 and mGlu 5 [Ballesteros-Weinstein numbering (Ballesteros and Weinstein, 1995) adopted from mGlu 1 structural alignment to family A GPCRs; Malherbe et al, 2003aMalherbe et al, ,b, 2006Muhlemann et al, 2006;Suzuki et al, 2007;Fukuda et al, 2009;Gregory et al, 2012Gregory et al, , 2013bGregory et al, , 2014Turlington et al, 2014;Wu et al, 2014]. Subsequently, key residues for the potency and/or binding of mGlu 1 , mGlu 2 , mGlu 4 , and mGlu 5 allosteric modulators from diverse chemical scaffolds have been mapped to TMs 3-7.…”
Section: The Common Mglu Allosteric Sitementioning
confidence: 99%
See 4 more Smart Citations
“…These mutagenesis studies pointed to a common location for allosteric binding pockets for group I mGlu receptors. Additional studies have shown that residues at positions 3.40 and 7.38 are important for allosteric modulation of both mGlu 1 and mGlu 5 [Ballesteros-Weinstein numbering (Ballesteros and Weinstein, 1995) adopted from mGlu 1 structural alignment to family A GPCRs; Malherbe et al, 2003aMalherbe et al, ,b, 2006Muhlemann et al, 2006;Suzuki et al, 2007;Fukuda et al, 2009;Gregory et al, 2012Gregory et al, , 2013bGregory et al, , 2014Turlington et al, 2014;Wu et al, 2014]. Subsequently, key residues for the potency and/or binding of mGlu 1 , mGlu 2 , mGlu 4 , and mGlu 5 allosteric modulators from diverse chemical scaffolds have been mapped to TMs 3-7.…”
Section: The Common Mglu Allosteric Sitementioning
confidence: 99%
“…Across the four subtypes multiple residues have repeatedly been reported as contributing to allosteric modulation. For all four subtypes, residues in positions 3.36, 5.43, and 6.48 are crucial for both positive and negative allosteric modulators (Pagano et al, 2000;Malherbe et al, 2003aMalherbe et al, , 2006Muhlemann et al, 2006;Fukuda et al, 2009;Lundstrom et al, 2011;Gregory et al, 2012Gregory et al, , 2013bGregory et al, , 2014Molck et al, 2012;Turlington et al, 2014;Wu et al, 2014;Rovira et al, 2015). Position 7.45 has also been implicated in mGlu 4 and mGlu 5 allosteric modulation (Molck et al, 2012;Gregory et al, 2013bGregory et al, , 2014Turlington et al, 2014;Rovira et al, 2015); there are no reports investigating the influence of this amino acid on selective allosteric modulators of mGlu 1 or mGlu 2 .…”
Section: The Common Mglu Allosteric Sitementioning
confidence: 99%
See 3 more Smart Citations